2011
DOI: 10.1128/jvi.05313-11
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Interaction between the Core and NS3 Proteins of Hepatitis C Virus Is Essential for Production of Infectious Virus

Abstract: By analogy to other members of the Flaviviridae family, the hepatitis C virus (HCV) core protein is presumed to oligomerize to form the viral nucleocapsid, which encloses the single-stranded RNA genome. Core protein is directed to lipid droplets (LDs) by domain 2 (D2) of the protein, and this process is critical for virus production. Domain 1 (D1) of core is also important for infectious particle morphogenesis, although its precise contribution to this process is poorly understood. In this study, we mutated am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 55 publications
(77 reference statements)
6
45
0
Order By: Relevance
“…In terms of replication, the NS3-5B region is sufficient to sustain viral RNA synthesis (12), and each of the proteins derived from this polyprotein is also known to contribute to virus production (30,(35)(36)(37)(38)(39)(40)(41)(42)(44)(45)(46)(47)(48). Our previous studies have shown that the kinetics of cleavage at boundaries between the NS proteins plays a critical role in reg- , and G1911A refer to the NS3-5B polyprotein expressed in the second cistron for each construct; wt denotes wt versions of NS5A and NS4B, S2208I indicates the mutation in NS5A, and G1911A denotes the mutation in NS4B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of replication, the NS3-5B region is sufficient to sustain viral RNA synthesis (12), and each of the proteins derived from this polyprotein is also known to contribute to virus production (30,(35)(36)(37)(38)(39)(40)(41)(42)(44)(45)(46)(47)(48). Our previous studies have shown that the kinetics of cleavage at boundaries between the NS proteins plays a critical role in reg- , and G1911A refer to the NS3-5B polyprotein expressed in the second cistron for each construct; wt denotes wt versions of NS5A and NS4B, S2208I indicates the mutation in NS5A, and G1911A denotes the mutation in NS4B.…”
Section: Discussionmentioning
confidence: 99%
“…Cell imaging shows that the RC lies proximal to sites where virus assembly probably occurs, since double-stranded RNA and MAF colocalize with envelope proteins and core-coated lipid droplets (30)(31)(32); the latter structures are thought to represent both a repository and a transitionary step in the maturation of core from a monomeric protein to a capsid shell (33,34). In addition, it has been conclusively demonstrated that mutations in the NS proteins can affect the efficiency of virus particle production independently of any effect that these changes may have on RNA replication (30,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Such data illustrate the tight link between viral RNA replication and virion assembly.…”
mentioning
confidence: 99%
“…Protein NS3 has been implicated in genome encapsidation as an RNP complex with the core protein to allow efficient budding of infectious particles. Both in HCV (20,21,56) and in yellow fever virus (22,23), the NS3 mutations rescuing impaired genomic RNP formation map to D1 and D2. In contrast, the mutations that rescue infectious pestivirus particle formation in the absence of a functional core protein (24) all map to D3 (Fig.…”
Section: Biochemical Characterization Of Csfv Ns3mentioning
confidence: 99%
“…In addition, NS3 was shown to play other functions in the virus cycle, such as interfering with the innate immune system in the case of HCV (18) and modulating fatty acid synthesis in the case of dengue virus (DENV) (19). It was also shown to participate in genome packaging and particle assembly in HCV (20,21), yellow fever virus (22,23), and pestiviruses (24). Indeed, an apparent interplay between genomic RNP formation and interactions with NS3 has been reported: CSFV virions lacking the core protein were found to be viable only when NS3 is mutated at specific locations.…”
mentioning
confidence: 99%
“…Furthermore, subdomains I and II of the NS3 helicase seemed to work together to promote HCV assembly because combination of an adaptive mutation, Q221N or I286V, in subdomain I and a second mutation, I399V, in subdomain II rescued virus production (26). Another study found that an adaptive mutation, K272R, in NS3 helicase could rescue virus production of defective HCVcc that has mutations in core protein (27). Recently, Kohlway and colleagues suggested that amino acids 171 to 194, located in a linker between the helicase and protease domains, also participate in HCV assembly (28).…”
Section: Discussionmentioning
confidence: 99%